Normarc Company / Mohd Farid Mohd Kamil... [et al.] - Mohd Kamil, Mohd Farid; Bahaudin, Asrul Nizam; Azemi, Azwadie; Ahmad Nasri, Azhar (2000)
The partnership is named NOMARC or northern mountaineering and Recreation Company. This business is set up to provide recreational facilities, finding the suitable site for the programmed, give information and guideline about the programme and give the student to fill up their free time in a proper way. Normarc Company has been form with 5 partners. It is a full bumiputra company that give services and sales equipment that based in adventure and challenging activities. This company located at Medan Kangar Top Floor, Kangar Perlis while their recreation site at Wang Mu, Perlis, Ulu Muda, Kedah and Gunung Jerai. The goal in their business is to make maximize profit and satisfied their customer with good services.